Patients' experiences of remote communication after pacemaker implant: The NORDLAND study - Catalán Matamoros, Daniel Jesús; López Villegas, Antonio; Lappegard, Knut Tore; López Liria, Remedios (PLOS ONE, 2019)
Supporting information: Variables, coding and anonymous data set: https://doi.org/10.1371/journal.pone.0218521.s001 Correction: https://doi.org/10.1371/journal.pone.0220828 The concept of 'patient experience' has become central to how to improve healthcare. Remote communication with patients is today a frequent practice in healthcare services, showing similar outcomes to standard outpatient care while enabling cost reduction in both formal and informal care. The purpose of this study was to analyse the experiences of people with telemonitoring pacemakers. This study has received financial support from the European Economic Area Grants –Science and Sustainability Program, ref. 008/ABELCM/2014A, received by DCM, and theConsejería de Salud, Junta de Andalucía, ref. PI/0256/2017, received by ALV.